2011
DOI: 10.1021/ol200360f
|View full text |Cite
|
Sign up to set email alerts
|

General Route to Symmetric and Asymmetricmeso-CF3-3(5)-Aryl(hetaryl)- and 3,5-Diaryl(dihetaryl)-BODIPY Dyes

Abstract: A general efficient route to hitherto inaccessible symmetric and asymmetric meso-CF(3)-BODIPY dyes has been developed. The key stages include the reduction of available 2-trifluoroacetylpyrroles to the corresponding alcohols which are further condensed with pyrroles. The method allows the BODIPY with 3(5)aryl(hetaryl) and 3,5-diaryl(hetaryl) substituents to be readily assembled. The BODIPY dyes synthesized fluoresce (Φ(f) = 0.56-1.00) in the 560-680 nm region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 48 publications
2
38
0
Order By: Relevance
“…[13] This approach allows both absorption and emission to be shifted by 100-200 nm towards red. [16] We have concisely reported that the presence of a CF 3 group in the meso-position of the BODIPY core does cause a deep bathochromic shift relative to congeners with other substituents in this position. [16] We have concisely reported that the presence of a CF 3 group in the meso-position of the BODIPY core does cause a deep bathochromic shift relative to congeners with other substituents in this position.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…[13] This approach allows both absorption and emission to be shifted by 100-200 nm towards red. [16] We have concisely reported that the presence of a CF 3 group in the meso-position of the BODIPY core does cause a deep bathochromic shift relative to congeners with other substituents in this position. [16] We have concisely reported that the presence of a CF 3 group in the meso-position of the BODIPY core does cause a deep bathochromic shift relative to congeners with other substituents in this position.…”
Section: Introductionmentioning
confidence: 85%
“…Very important shifts towards the NIR end of the visible spectra have been recently achieved by introducing a strong electron acceptor such as pentafluorobenzene [14] or CF 3 [15,16] at the meso-position of the BODIPY core, though the asymmetrical representatives with a meso-CF 3 moiety can only be synthesized by using a specific methodology. [16] Despite this progress, synthesis of new meso-CF 3 -BODIPY derivatives with aryl groups remains challenging because the fluorescence maxima of BODIPY strongly depend on the nature of the aryl substituent. [16] Despite this progress, synthesis of new meso-CF 3 -BODIPY derivatives with aryl groups remains challenging because the fluorescence maxima of BODIPY strongly depend on the nature of the aryl substituent.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous aromatic and aliphatic substituents have been used to modify the BODIPY core. Substitution at the 2,6 and 3,5 positions has been widely used to extend conjugation [9][10][11][12]. Substitution at the meso position and boron center does not cause significant shift in absorption and emission spectra [13].…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] The substitution of heteroaromatic residues, especially in the 3,5 positions, endow to the BODIPYs significant red shifted spectral transitions. [20][21] We have previously demonstrated that 3,5-dithienyl BODIPYs [22][23][24] exhibit comparable red shifted emission with respect to the 3,5-diphenyl analogue. [23][24] There are even fewer examples of oligothiophenes attached to BODIPY derivatives, [25][26][27][28][29] some being those with oligothiophenes attached in the meso position to give donor/acceptor materials.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21] We have previously demonstrated that 3,5-dithienyl BODIPYs [22][23][24] exhibit comparable red shifted emission with respect to the 3,5-diphenyl analogue. [23][24] There are even fewer examples of oligothiophenes attached to BODIPY derivatives, [25][26][27][28][29] some being those with oligothiophenes attached in the meso position to give donor/acceptor materials. We recently reported the grafting of short conjugated oligothiophene chains to the 3,5 positions of BODIPY derivatives.…”
Section: Introductionmentioning
confidence: 99%